A study into syngas production from catalytic steam reforming of palm oil mill effluent (POME): A new treatment approach - Ng, Kim Hoong; Cheng, Yoke Wang; Lee, Zhan Sheng; Cheng, C. K. (Elsevier, 2018)
This paper reports on the novel application of catalytic steam reforming process to convert palm oil mill effluent (POME) into syngas over a 20wt% Ni/80wt% Al 2 O 3 catalyst. The catalyst possessed high degree of crystallinity and was impurity-free, judging from the obtained XRD pattern. Furthermore, the BET specific surface area of catalyst was low (2.09 m 2 g− 1), consistent with smooth surface captured by the FESEM images. CO 2-desorption and NH 3-desorption profiles showed a presence of both acid and basic sites on the surface of catalyst. In the absence of catalyst, about 7.0% reduction of chemical oxygen demand (COD) was achieved at 6.0 mL h− 1 flow rate of POME, reforming temperature of 873 K and 20 mL min− 1 of N 2-flow. Significantly, the COD reduction shot up to 93.7% in the presence of catalyst and liquid-hourly-space-velocity (LHSV) of POME of 90 mL h− 1 g cat− 1 at 873